Paradigma Kritisisme dalam Pemikiran Islam Kontemporer: Analisis Filosofis dan Implikasi Metodologis - Adhimas Bagaskara; Figlia Mutmainnah Syakura; Rifa Hanifah; M. Rid Fadhilah; Muhamad parhan (CV. ITTC INDONESIA, 2025)
This article examines the paradigm of criticism in contemporary Islamic thought with a focus on philosophical analysis and its methodological implications. Through a literature study approach, this study explains how criticism as an epistemological paradigm develops in Islamic thought, which emphasizes the integration of reason, revelation, and experience. The study is conducted on the theoretical basis of criticism that originated from Kant's thought, then how the paradigm evolved and was adapted in the context of Islamic thought with distinctive characteristics. The results of the analysis show that the paradigm of criticism in contemporary Islamic thought has a distinctive feature in the form of a